American tripanosomiasis, a new look at its treatment - Sánchez, Emmanuel (2016)
American trypanosomiasis or Chagas disease is a parasitic infection caused by the flagellate parasite Trypanosoma cruzi, whose main vector is an insect of the Hemiptera class, called triatomine. Chemotherapy, in addition to an appropriate vector control and a rigorous control of transfusions, are the most important strategies for the management of this parasitosis. Currently, the pharmaceutical market only offers nifurtimox and benznidazole as treatment options, and although satisfactory results have been obtained with the use of these drugs in either acute stages of the disease, congenital trypanosomiasis and laboratory accidents, its effectiveness in the chronic phases is significantly smaller. In addition, both drugs produce some side effects that must be taken into account by health workers, before starting the proper management of the disease. The aim of this article is to review the current state of the American trypanosomiasis treatment, in order to summarize the new advances in therapeutics and to introduce their limitations due to adverse effects.